Perkembangan dan Usaha Pengembangan Dadih: Sebuah Review tentang Susu Fermentasi Tradisional Minangkabau - A.A. Putra; Y. Marlida; Khasrad Khasrad; S.Y.D. Azhike; R. Wulandari (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
Dadih is a traditional fermented milk of Minangkabau ethnic which has been part of the richness of Indonesian food. Its existence has united with society life in West Sumatra, especially for community who resides in buffalo utilization areas. Here, some of buffalo milk productions are taken for dadih manufacturing. However, the production of dadih is still limited and does not show any immense progress so far. This review explains some aspects related to basic understanding about dadih, real condition of dadih production, the limitation of dadih’s production development and its consumption level, and completing with some dadih-related-researches and other potential attempts which are used as temporary answers to overcome low level of those conditions. Application of various researches on market scale is hoping to be the real response to force modern commercialization of dadih production and as a final point to enhance the level of dadih consumption.